‘Despite the Fear’: Emancipation Trajectories in Libya, 1890–1930 - (:unkn) unknown (My University, 2022)
Challenging the Eurocentric belief that abolitionism was a top-down process issued by colonial powers, this article explores the emergence of personal and group strategies for the emancipation of Black enslaved people in Libya. During the late Ottoman period, Italian antislavery activities operated in Libya and established a mission in Benghazi to host manumitted children referred to as ‘Moretti ’ (‘little Moors’). The goal was to make these Moretti a group of local people close to the Catholic Church and the Italian government. The failures of the missionaries to accomplish these aims reveal the strategies and trajectories of Moretti as they negotiated their role in society, especially after Italian occupation in 1911. Historical sources reveal an informal web of solidarity using antislavery societies and creating forms of urban and social autonomy. This article details actions of solidarity among Black enslaved persons that took place in late Ottoman and Italian colonial Libya, which challenges Eurocentric antislavery narratives.
Keywords: African Research